Analysis of CAPM and SAPM Models in Predicting Return of Islamic Stock (Case Study of Islamic Stocks in the Jakarta Islamic Index) for the 2017-2021 Period - Anwar, Moh Muhlis (Mabny: Journal of Sharia Management and Business, 2023)
In the investment world there are rational and irrational investors, rational investors use mature calculation steps in investment decisions and predict stock returns so that this is the forerunner of the emergence of CAPM, while irrational investors only follow their own instincts, psychology and investor proxies in predicting and making investment decisions without careful consideration, so SAPM emerged. Basically, the CAPM and SAPM models are no different, the only difference is the beta, beta SAPM uses beta modification, namely beta investor sentiment. This study uses a quantitative descriptive approach to describe which is more accurate between CAPM and SAPM in predicting expected returns, namely by using the Mean Absolute Deviation (MAD) test. The results of this study can be concluded that the CAPM model is more accurate than the SAPM model.